Examining Social Support Among Adult Children of Incarcerated Parents. Issue 4 (4th September 2015) - Luther, Kate
Abstract : Parental incarceration is related to many challenges and risks, yet we know little about resilience among this population. This study examined how social support contributed to the resilience of a sample of adult children of incarcerated parents. In‐depth qualitative interviews were conducted with 32 college students who had experienced parental incarceration during their childhoods. Social support from caring adults, including caregivers, incarcerated parents, grandparents, older siblings, teachers, and coaches helped facilitate success in light of parental criminality and incarceration. In particular, these adults promoted resilience in 3 ways: (a) providing access to conventional activities, (b) supporting a vision of a better life, and (c) encouraging turning points. Implications for those who work with children of incarcerated parents are discussed.